(untitled) (Anclajes, 2025)
La pareja de Núñez is a novel by Gloria Alcorta Mansilla published by Editorial Sudamericana in 1971. Framed in two chapters that can represent an entire year, a narrator anticipates and then closes the stories told. Núñez is the setting in which a series of plebeian characters and archetypes live, linked by misfortunes linked by class and gender conflicts. Immigration, exile, abuse, abandonment, poverty, and even militant courage and poetry are part of the imaginary of this community that includes and excludes the bodies of its inhabitants. The use that the text makes of the fantastic genre, as well as the relationship of this novel with the author’s work and with the local literary tradition constitute the axes of analysis.